Chloride anion effect on the advanced oxidation processes of methidathion and dimethoate: role of Cl₂˙⁻ radical - Caregnato, Paula (2013)
The reaction of phosphor-containing pesticides such as methidathion (MT) and dimethoate (DM) with dichloride radical anions (Cl₂˙⁻) was investigated. The second order rate constants (1.3 ± 0.4) × 10⁸ and (1.1 ± 0.4) × 10⁸ M⁻¹ s⁻¹ were determined for the reaction of Cl₂˙⁻ with MT and DM, respectively. A reaction mechanism involving an initial charge transfer from the sulfide groups of the insecticides to Cl₂˙⁻ is proposed and supported by the identified transient intermediates and reaction products. The formation of chlorinated byproducts was determined. The unexpected consequences of an efficient Cl₂˙⁻ reactivity towards MT and DM on the degradation capacity by Advanced Oxidation Procedures applied to polluted waters containing the insecticides and Cl⁻ anions is discussed.